A gravitációs modell alkalmazási lehetőségei a településen belüli mozgások tanulmányozására - Nagy, Gábor (Tér és Társadalom, 1996)
In this study we make an attempt to apply the gravity modell, to reveal the reasons some types of movements inside the city. This model wants to show that in the retail trade in Győr how strong attractions are among the main parts of the city. The results of our analysis shows that the internal structure of the city Győr is rather far from an ideal one by the attraction generated the retali trade sector. The importance of the CBD is too big in the movements of retail trade intention. It’s not suitable for the planned future of the inner city, which wants to exempt this district from the traffic. And this CBD is rather small, and restricted by the rivers and the railway. There is some way to purify our modell. We must take the groups of commodities dissociate into consideration, because it give us a chance to separate the daily, weekly and rare shoppings, so we get a cleaner portrait about the intensity of connections among the main parts of the city.